Maternal high-fat diet decreases milk endocannabinoids with sex-specific changes in the cannabinoid and dopamine signaling and food preference in rat offspring - Dias-Rocha, Camilla P.; Costa, Julia C. B.; Oliveira, Yamara S.; Fassarella, Larissa B.; Woyames, Juliana; Atella, Georgia C.; Santos, Gustavo R. C.; Pereira, Henrique M. G.; Pazos-Moura, Carmen C.; Almeida, Mariana M.; Trevenzoli, Isis H. (Frontiers in Endocrinology, 2023)
Introduction: Maternal high-fat (HF) diet during gestation and lactation programs obesity in rat offspring associated with sex-dependent and tissue-specific changes of the endocannabinoid system (ECS). The ECS activation induces food intake and preference for fat as well as lipogenesis. We hypothesized that maternal HF diet would increase the lipid endocannabinoid levels in breast milk programming cannabinoid and dopamine signaling and food preference in rat offspring. Methods: Female Wistar rats were assigned into two experimental groups: control group (C), which received a standard diet (10% fat), or HF group, which received a high-fat diet (29% fat) for 8 weeks before mating and during gestation and lactation. Milk samples were collected to measure endocannabinoids and fatty acids by mass spectrometry. Cannabinoid and dopamine signaling were evaluated in the nucleus accumbens (NAc) of male and female weanling offspring. C and HF offspring received C diet after weaning and food preference was assessed in adolescence. Results: Maternal HF diet reduced the milk content of anandamide (AEA) (p<0.05) and 2-arachidonoylglycerol (2-AG) (p<0.05). In parallel, maternal HF diet increased adiposity in male (p<0.05) and female offspring (p<0.05) at weaning. Maternal HF diet increased cannabinoid and dopamine signaling in the NAc only in male offspring (p<0.05), which was associated with higher preference for fat in adolescence (p<0.05). Conclusion: Contrary to our hypothesis, maternal HF diet reduced AEA and 2-AG in breast milk. We speculate that decreased endocannabinoid exposure during lactation may induce sex-dependent adaptive changes of the cannabinoid-dopamine crosstalk signaling in the developing NAc, contributing to alterations in neurodevelopment and programming of preference for fat in adolescent male offspring.